The key enablers of competitive advantage formation in small and medium enterprises: The case of the Ha’il region - Thomran, Murad; Alshallaqi, Mohammad; Al-Mamary, Yaser Hasan; Abdulrab, Mohammed (Frontiers in Psychology, 2022)
The primary objective of this research is to establish the extent to which small and medium-sized businesses (SMEs) in the Ha’il region benefit from a significant competitive advantage brought about by an entrepreneurial mindset (innovativeness, proactiveness, risk-taking, competitive aggressiveness, and autonomy). To achieve these objectives, the study used a questionnaire to collect data. A total of 220 SMEs in the Ha’il region were surveyed. The participants completed an online self-administered survey and used the PLS-SEM technique. The researchers found a robust link between differentiation advantage and higher levels of innovativeness, proactiveness, risk-taking, competitive aggression, and autonomy. In addition, the outcomes of the survey reveal that a greater cost advantage is substantially associated with vastly greater innovativeness, proactiveness, risk-taking, and competitive aggression overall. However, cost advantage is not strongly correlated with autonomy. These findings are significant because they shed new light on how competitive advantages are formed through the entrepreneurial orientation of entrepreneurs in the Ha’il region. This is a significant theoretical contribution to the literature on entrepreneurial orientation, specifically in the context of SMEs. The findings may also be valuable in supporting SMEs in being successful by enhancing their competitiveness, as SMEs are key contributors to the development and growth of the economy.